2019
DOI: 10.1039/c8ra08380k
|View full text |Cite
|
Sign up to set email alerts
|

Pinostrobin inhibits proliferation and induces apoptosis in cancer stem-like cells through a reactive oxygen species-dependent mechanism

Abstract: The anti-proliferative potential of pinostrobin, a dietary flavonoid, is evaluated against cancer stem-like cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Our FDNVs contained alkaloids, phenolics, lipids, and organic compounds, which illustrates the diversity of phytochemical constituents in FDNVs. There have been reports of anticancer potentials of phenolic compounds via ROS-mediated apoptosis, such as naringenin chalcone [ 36 ], pinostrobin [ 37 ], and pinocembrin [ 38 ]. In addition, valerenic acid (lipid) and darymid A (alkaloid) have also been found to possess anticancer activity [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our FDNVs contained alkaloids, phenolics, lipids, and organic compounds, which illustrates the diversity of phytochemical constituents in FDNVs. There have been reports of anticancer potentials of phenolic compounds via ROS-mediated apoptosis, such as naringenin chalcone [ 36 ], pinostrobin [ 37 ], and pinocembrin [ 38 ]. In addition, valerenic acid (lipid) and darymid A (alkaloid) have also been found to possess anticancer activity [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The secondary metabolites present in plants, such as flavonoids, fatty acids, and proteins have been shown to induce ROS generation, i.e. pinostrobin [ 37 ], linoleic acid [ 50 ], and phospholipase D [ 51 ], respectively. Our study showed that ROS levels were elevated in HT-29 and HCT116 cells after FDNVs treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the ability of pinostrobin to prevent the cyclooxygenase enzyme pathway indicates anti-inflammatory potential [ 27 ]. In addition, pinostrobin has significant effects on cell cycle arrest, growth inhibition, and apoptosis in many cancers [ 48 ]. Jaudan et al demonstrated that HeLa cells are more sensitive to pinostrobin than other cancer cell lines in vitro [ 27 ].…”
Section: Clinically Available Natural Productsmentioning
confidence: 99%
“…Pinostrobin (PN) (Fig. 1d) is one of the most flavones found in fingerroot (Boesenbergia rotunda) and honey which is commonly potential as an antioxidant and contribute against several diseases (Fahey and Stephenson, 2002;Chahyadi et al, 2014;Patel et al, 2016;Atun et al, 2017;Jadaun et al, 2019). Even though there are few numbers of reports regarding pinostrobin, some are reported to have roles to some cancers, such as in breast cancer by binding with estrogen receptor and fibrosarcoma by upregulating the expression of p53 and decreasing activation of VEGF angiogenesis (Le Bail et al, 2000;Parwata et al, 2015).…”
Section: Pinostrobinmentioning
confidence: 99%